A Rising Tide Does Not Lift All Boats: Intersectional Analysis Reveals Inequitable Impacts of the Seafood Trade in Fishing Communities - Ferguson, Caroline E. (Frontiers in Marine Science, 2021)
Seafood is the world’s most traded food commodity, and the international trade in seafood is promoted as a development strategy in low-income coastal communities across the globe. However, the seafood trade can drive negative social and environmental impacts in fishing communities, and whether the benefits of trade actually reach fishers is a subject of ongoing scholarship. Furthermore, scholars and policymakers have tended to treat fishing communities as homogeneous, assuming that trade policies will impact all members equally. Yet individual community members have different roles, statuses, and entitlements according to their intersecting identities, meaning that different fishers will be differently impacted by the seafood trade. In particular, women occupy different positions than men in seafood value chains and in fishing communities. There are also important within-group differences among men and among women depending on their nationality, marital status, and other identity markers. Through 205 surveys, 54 interviews, and ethnographic field methods conducted in fifteen rural Palauan fishing communities between November 2019 and March 2020, this case study of the sea cucumber trade in Palau brings together theories of gender, intersectionality, and access to answer the question, “How are the harms and benefits of the seafood trade distributed in fishing communities?” In this case, men benefited more than women from the export of sea cucumbers by leveraging access to technology; knowledge; and authority, and the trade depleted resources relied on primarily by women for their food security and livelihoods. An intersectional analysis revealed that marital status and nationality determined access among women, with married women having greater access than unmarried women and immigrant women having greater access than immigrant men, demonstrating the importance of intersectionality as an analytical tool.